Refiguring the Primitive: Institutional Legacies of the Filmology Movement - Bloom, Peter (Cinémas, 2009)
AbstractThis contribution examines how the discourse of “the primitive,” as an institutional point of reference developed by the philosopher Lucien Lévy-Bruhl (1857-1939), influenced the establishment of the Institute of Filmology at the University of Paris in 1948. Filmology, a term introduced by Gilbert Cohen-Séat, is described as a positive science with its own strategy of systematizing the study of film as object and institution with its own series of emerging methods. The present article describes the formulation of the “filmic fact” as a positive science indebted to Durkheimian methods, but also as a means of engaging with the multiple strands of “primitivism.” On the one hand, this article elaborates upon the significance of Lévy-Bruhl’s discussion of “primitivism” as an effective cosmology for causation and related inferences which asserts a space of difference to be further explored, and on the other, it explains how “primitivism” has been used to designate historical and psychological attributes within the institution of cinema as an emerging structure of producing meaning.